Predictive spatial modelling and distribution mapping of Bornean Banteng (Bos javanicus lowi) in Sabah, Malaysia - Lim, Hong Ye (2017)
Habitat fragmentation and poaching threatens the Bornean banteng ( Bos Javanicus low,) population within Sabah. The first banteng distribution map was published by Davies and Payne in 1982 using community surveys. A lack of up-to-date information on their current distribution prevents effective conservation and management, and mitigation against the threats. Using quantitative data from camera traps, this study modelled and mapped the habitat suitability of Bornean banteng within Sabah using two species distribution modelling methods: 1) Maximum Entropy (MaxEnt) and 2) Boosted Regression Trees (BRT), to compare their predictive power. Fifty-eight presence and 182 absence of banteng were modelled with twelve environmental predictors, and the predictive power of the models were tested with cross-validation and independent data. Cross-validation AUC values were high for MaxEnt (0.932 ± S.D 0.041), and intermediate for BRT (0.719 ± S.E 0.419), similarly the independent testing AUC values were high for MaxEnt (0.939), and intermediate for BRT (0.713). The most influential environmental predictors for both models were precipitation during driest quarter (MaxEnt: 21.6% and BRT: 31.4%). Tabin Wildlife Reserve was predicted as suitable in the MaxEnt model, however was not suitable in the BRT model. Habitat that receives rainfall between 550 to 600 mm during the driest quarter of the year, and these areas should be targeted for conservation. The MaxEnt model illustrated the central forest and Ulu Tungud Forest Reserve are suitable for banteng. The central reserve is the largest forest patch in Sabah and is highly suitable for banteng; it is essential that the connectivity between forests in this central area is maintained for gene flow and dispersal. The banteng in Tabin Wildlife Reserve are highly fragmented however the nearby forest Kulamba Wildlife Reserve has suitable habitat, therefore a potential wildlife corridor could be developed between these areas.